2019
DOI: 10.21037/tp.2019.01.06
|View full text |Cite
|
Sign up to set email alerts
|

The difference in extraintestinal manifestations of inflammatory bowel disease for children and adults

Abstract: Extraintestinal manifestations (EIMs) are frequently observed in adult and pediatric patients with inflammatory bowel disease (IBD). The most common EIMs involve the joints, skin, and eyes, but they can affect various organs and result in significant morbidity. Since EIMs can appear years before the diagnosis of IBD is made, clinicians should be aware of their various manifestations to help decrease diagnostic delay of IBD and establish appropriate treatment plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
1
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 112 publications
(162 reference statements)
0
36
1
16
Order By: Relevance
“…Dermatological manifestations are seen in children with both CD and UC, their incidence varying from 10–15% [ 4 ]. They are either specific or reactivation lesions or may be related to malabsorption or drugs used in the treatment of IBD; a small group of lesions have been described in the literature concomitant to IBD but are considered miscellaneous lesions ( Table 1 ) [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Dermatological manifestations are seen in children with both CD and UC, their incidence varying from 10–15% [ 4 ]. They are either specific or reactivation lesions or may be related to malabsorption or drugs used in the treatment of IBD; a small group of lesions have been described in the literature concomitant to IBD but are considered miscellaneous lesions ( Table 1 ) [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…Usually, it is located on the extensor surfaces of the extremities; in the pediatric population, PG has been reported more often on the legs, followed by the head and the gluteal region. It has been reported in 0.3–5% of patients with IBD [ 4 ]. The authors reported that PG is more common in children with CD than UC, and is related mostly to the colonic involvement, presence of erythema nodosum, and arthritis [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations